CD4+ T cells support polyfunctionality of cytotoxic CD8+ T cells with memory potential in immunological control of tumor. Issue 6 (12th May 2020) - Imai, Naoko; Tawara, Isao; Yamane, Makiko; Muraoka, Daisuke; Shiku, Hiroshi; Ikeda, Hiroaki
Abstract: Polyfunctionality/multifunctionality of effector T cells at the single cell level has been shown as an important parameter to predict the quality of T cell response and immunological control of infectious disease and malignancy. However, the fate of polyfunctional CD8 + CTLs and the factors that control the polyfunctionality of T cells remain largely unknown. Here we show that the acquisition of polyfunctionality on the initial stimulation is a sensitive immune correlate of CTL survival and memory formation. CD8 + T cells with high polyfunctionality, assessed with γ‐interferon and tumor necrosis factor‐α production and surface mobilization of the degranulation marker CD107a, showed enhanced Bcl‐2 expression, low apoptosis, and increased CD127 high KLRG1 low memory precursor phenotype. Consistent with these observations, CD8 + T cells were found to acquire high frequency of cells with polyfunctionality when stimulated in conditions known to enhance memory formation, such as the presence of CD4 + T cells, interleukin (IL)‐2, or IL‐21. Utilizing T‐cell receptor (TCR) transgenic mouse‐derived CD8 + T cells that express a TCR specific for a tumor‐derived neoantigen, we showed that polyfunctional tumor‐specific CTLs generated in the presence of CD4 + T cells showed long persistence in vivo and induced enhanced tumor regression when adoptively transferred into mice with progressing tumor. Acquisition of polyfunctionality thus impacts CTL survival and memory formation associated with immunological control of tumor. Abstract : We report that polyfunctional CD8 + T cells showed the potential for long survival and memory formation. We found that CD4 + T cells, interleukin (IL)‐2, and IL‐21 exert a critical effect on the determination of polyfunctionality of CD8 + T cells. Polyfunctional tumor‐specific CTLs generated in the presence of CD4 + T cells showed long persistence in vivo and induced enhanced tumor regression when used for adoptive immunotherapy.